Basic Sanitation Profile of the Community in Doyado Village, Tidore Islands City - Suryadi M Ali; Nursita Syahruddin; Naila Ridha Awalia R. Abbas; Siti Nurcholifatun Musiam; Muhlisa MT. Sisway; Marsyah M. Tobona (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Environmental health is an ideal condition that has a positive impact on public health, including housing, waste disposal, clean water supply, and wastewater and solid waste management. Inadequate waste management, low ownership of wastewater disposal systems, and limited basic sanitation education are the main problems of environmental sanitation in Doyado Village. The purpose of this study is to describe the basic sanitation conditions of the community in Doyado Village, Tidore City in 2025. The research method used is a descriptive approach. The study population includes all 292 census buildings in Doyado Village. The study sample consisted of 169 households selected by stratified random sampling. The results showed significant results. The majority of households use protected dug wells as their primary water source (85 households (50.3%). Fifty-eight households (34.3%) do not treat their drinking water before consumption. Most households in Doyado Village have private toilets used exclusively by their own family members (129 households (76.33%). The most common method of waste disposal is burning (38.5%). Another relatively common method is throwing waste into rivers or waterways, at 24.9%. Community efforts to prevent mosquito-borne diseases are dominated by the use of mosquito coils, mosquito spray, or electronic mosquito repellents, which are used by 82.8% of the 169 households. It is recommended that local governments and communities collaborate to implement sanitation improvement programs, including the implementation of hygienic sanitation practices, to achieve a healthy and sustainable environment.